Integrated Analysis of Transcriptome and Proteome to Reveal Pupal Color Switch in Papilio xuthus Butterflies - He, Jin-Wu; Dong, Zhi-Wei; Hu, Ping; Liu, Wei; Zhang, Ru; Liu, Gui-Chun; Zhao, Ruo-Ping; Wan, Wen-Ting; Wang, Wen; Li, Xue-Yan (Frontiers in Genetics, 2022)
Pupal color polyphenism in Papilio butterflies, including green, intermediate, or brown, is an excellent study system for understanding phenotypic plasticity. Previous studies suggested that development of brown pupae may be controlled by a hormone called pupal-cuticle-melanizing-hormone (PCMH) which is synthesized and secreted from brain-suboesophageal ganglion and prothoracic ganglion complexes (Br-SG-TG1) during the pre-pupa stage. However, detailed molecular mechanisms of neuroendocrine regulation in pupal color development remain unknown. In this study, we integrated the expression profiles of transcriptome and proteome at pre-pupa stages (2 h after gut purge (T1) and 3 h after forming the garter around the body (T2)) and pigmentation stages (10 h after ecdysis (T3) and 24 h after ecdysis (T4)) to identify important genes and pathways underlying the development of green and brown pupa in the swallowtail butterfly Papilio xuthus. Combined comparisons of each developmental stage and each tissue under green and brown conditions, a total of 1042 differentially expressed genes (DEGs) and 430 different abundance proteins (DAPs) were identified. Weighted gene co-expression network analysis (WGCNA) and enrichment analysis indicate that these DEGs were mainly related to oxidation-reduction, structural constituent of cuticle, and pigment binding. Soft clustering by Mfuzz and enrichment analysis indicate that these DAPs are mainly involved in tyrosine metabolism, insect hormone biosynthesis, and melanogenesis. By homologous alignment, we further identified those genes encoding neuropeptides (51), GPCRs (116), G-proteins (8), cuticular proteins (226), chitinases (16), and chitin deacetylases (8) in the whole genome of P. xuthus and analyzed their expression profiles. Although we identified no gene satisfying with hypothesized expression profile of PCMH, we found some genes in the neuropeptide cascade showed differentially expressed under two pupal color conditions. We also found that Toll signaling pathway genes, juvenile hormone (JH) related genes, and multiple cuticular proteins play important roles in the formation of selective pupal colors during the prepupal-pupal transition. Our data also suggest that both green and brown pupa include complex pigment system that is regulated by genes involved in black, blue, and yellow pigments. Our results provide important insights into the evolution of pupal protective colors among swallowtail butterflies.